Study on total lipid content, lipid class composition of some fire and soft corals collected in Nha Trang, Vietnam - Kien, Nguyen Ba; Huong, Trinh Thi Thu; Huyen, Luu Van; Vinh, Nguyen Thanh; Phong, Tran Duy; Nguyet, Dang Thi Minh; Nga, Nguyen Thi; Ly, Dang Thi Phuong; Long, Pham Quoc (Vietnam Journal of Marine Science and Technology, 2019)
For the first time, the total lipid content and lipid class composition of the Vietnamese soft corals (Sinularia brassica, Sinularia flexibilis) and fire corals (Millepora dichotoma, Millepora platyphylla) were investigated. The results indicated that the total lipid content of the investigated species was significantly different. Compositions of the lipid classes were analyzed using TLC and image analysis program Sorbfil TLC Videodensitometer DV and the results showed that phospholipids (PL, 10.91–16.02%), monoalkyldiacylglycerols (MADAG, 20.69-39.92%) and hydrocarbon wax (HW, 29.83-37.17%) were the main lipid classes of the total lipid in soft coral species. Meanwhile, PL (24.11-33.23%), TG (14.27–34.92%), ST (10.10–14.50%) and HW (12.08–19.95%) were predominant in fire coral species. ST, TG and FFA contents in soft and fire corals were at low level. DG was only present in the Sinularia flexibilis but not in other studied corals